ALADEEN’S FACE-THREATENING ACTS REFLECTED IN THE DICTATOR MOVIE’S DIALOGUES - ARISTY, DANIAR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key words: Face-threatening acts (FTAs), positive face, negative face, context. Making interaction or socialization with other people to gain something such as information is natural for everyone. Thus, people want to be accepted or liked by society in many ways in which one of them is through communication. However, there are some utterances that cannot be accepted by some people and study of face-threatening acts (FTAs) of pragmatics is needed to analyze the utterances. The researcher conducted a study of FTAs in ‘The Dictator’ movie (TD) which performs FTAs phenomena occuring in the main character’s dialogues. In order to describe the context of the movie scenes, the researcher used a theory of Hymes. There are two problems to be solved, namely: (1) utterances of the main character containing face-threatening acts and (2) the kinds of face-threatening acts are used by the main character in threatening the negative face and the positive face. In this study, the researcher applied qualitative method since the data were transcribed utterances containing face-threatening acts from the main character in TD movie. The researcher also applied descriptive method in which is a research method that uses a technique of searching, collecting, classifying, analyzing the data, interpreting them and then drawing the conclusion in conducting an analysis of the main character’s utterances and the scenes of TD movie. This study reveals that the main character’s utterances containing FTAs by using positive FTAs and negative FTAs. Based on the analysis, the main character’s utterances perform some FTAs, either from positive face and negative face, in order to threat the hearers’ face. The main character does not fulfill the hearer’s desire or feeling in order to get his want of freedom. Later, the chosen scenes of the movie are elaborated by using context theory.